EFFECTIVENESS OF POLYVITAMINS COMPLEX IN INFANTS WITH ORGANIC DISEASES OF INTESTINE - O.G. Shadrin; S.V. Dyukareva-Bezdenezhnykh ("Paediatrician" Publishers LLC, 2010)
One of the largest risk groups of hypovitaminosis development are children with prolonged gastroenterological diseases. This problem is significant in infants, because they can develop prolonged enterocolitis conditioned by opportunistic micro flora which results in severe dysbacteriosis, delay of development and beginning of dystrophy. Normal micro flora is one of the sources of vitamins (especially B group). Besides, inflammation in intestine results in disorder of digestion and absorption processes, and it can break metabolism of different nutrients. Authors present results of treatment of organic intestinal diseases with syrup «Picovit». Key words: children, enterocolitis, polyvitamins. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):85-89)